CASE STUDY: HOUSEHOLD FACTORS AND ELDERLY WORK DECISIONS IN INDONESIA - Silvia Margaret; Putri Patria Kusuma (Universitas Negeri Semarang, 2025)
Indonesia is one of the countries with a large elderly population. The high participation rate of the elderly workforce can cause this. This kind of challenge, if it does not receive special attention from the government, can cause several new problems, especially in the issue of employment. Therefore, this study was conducted to see how household characteristics influence the decision of older people to work. The data used in this study is sourced from the Indonesian Family Life Survey (IFLS) 5th wave. The methodology used in this paper is a logit econometric model. This logit model is used because the dependent variable from this study is a dummy variable. From the analysis results, evidence was found that household characteristics, such as the type of work, education level, marital status, health status, and residential area status, significantly impact the decision of older people to work. By understanding the characteristics of households that influence older people's decision to work, we can design more effective policies and programs to support older people and ensure their well-being, especially at retirement age, such as pension schemes and social protection programs.